2023
DOI: 10.1177/15347354231198090
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Plasma Metabolites From Patients With Non-Small Cell Lung Cancer by Erlotinib Treatment and Skin Rash

Won Kil Lee,
Jisoo Myong,
Eunbin Kwag
et al.

Abstract: Erlotinib is a necessary anticancer treatment for non-small cell lung cancer (NSCLC) patients yet it causes severe side effects such as skin rash. In this study, researchers compared the untargeted compound profiles before and after erlotinib administration to observe changes in blood metabolites in NSCLC patients. The levels of 1005 substances changed after taking erlotinib. The levels of 306 and 699 metabolites were found to have increased and decreased, respectively. We found 5539 substances with peak area … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The study's findings demonstrated that the apoptosis proteins Fas, bax and FasL in the ERG were higher than the NSG, and the Bcl-2 were lower than the NSG. It has been found that erlotinib can induce apoptosis in NSCLC cancer cells through the mitochondrial pathway [16] .…”
Section: Groupmentioning
confidence: 99%
“…The study's findings demonstrated that the apoptosis proteins Fas, bax and FasL in the ERG were higher than the NSG, and the Bcl-2 were lower than the NSG. It has been found that erlotinib can induce apoptosis in NSCLC cancer cells through the mitochondrial pathway [16] .…”
Section: Groupmentioning
confidence: 99%